Letter (copy) - Gomez Osorio, Jose
1934-10-26 COPY. Madrid, 26 October 1934. I reply to your letter of the 22nd, and have unfortunately to confirm what I anticipated. The rising has been completely suffocated and defeated by the Government, without it yet being possible for me to say, at the present moment, what the consequences may be for the organizations and for persons. The reactionary elements in this country are calling upon the Government to impose punishments of a severe and exemplary nature - as they call it - and if their demands were met they would certainly not be satisfied with anything less than the complete demolition of all political and trade union organizations of the Spanish working class, and the hanging of all their leaders without exception, whether or not they had anything to do with the preparation and leadership of the revolutionary movement. I have the impression, however, that they are finding a powerful brake to their wishes in the President of the Republic, and there is already talk of a political crisis arising because the President is opposed to anybody being shot for sedition or rebellion, and is apparently only prepared to agree to the shooting of those who, in addition to these crimes, have also been guilty of the murder of civilians; or of members of the public forces after martial law was declared. In this respect I am optimistic, but I do not think that the danger of a military dictatorship has disappeared, since although many commanders and officers of the Spanish army regard a military dictatorship as an absurdity, there are still generals who think otherwise, and who are just now very much upset at the heavy losses suffered by the army and other armed forces. Things are bad for us for the moment, but we are by no means dismayed. You may rest assured that our pulse is beating normally and our heads are as cool as when everything is going normally. I am giving much thought to the future of the whole labour and socialist movement, and am ready to step in and act as soon as I can, provided that that is the wish of the workers. I am thinking more particularly of the Sindicato Nacional Ferroviario (National Union of Railwaymen), a few of whose leading personalities are urging me to return to the general secretaryship. This is a wish which I naturally welcome and am grateful for, but for the time being I have nothing more to say, since I can still be very useful to the Union without returning to the job, and in this I am sparing no effort. Copied EKK/5.11.34. 292/946/9/54